PEMAHAMAN DAN KESIAPAN GURU MATA PELAJARAN BAHASA INDONESIA SMK KABUPATEN TEGAL DALAM MENDUKUNG IMPLEMENTASI KURIKULUM 2013 - GHUFRONI, GHUFRONI (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2018)
This study aims to determine the understanding and readiness of Indonesian Vocational School teachers in Tegal Regency in implementing the 2013 Curriculum. This research is a quantitative descriptive study. Respondents in this study were teachers of Indonesian Language Vocational School in Tegal Regency who had implemented the 2013 Curriculum. The results showed that Teacher's understanding of Curriculum 2013 was in the moderate category, namely as many as 12 teachers (48%). Teachers who were included in the low category were 8 teachers (32%), and teachers who were included in the high category were 5 teachers (20%). While the readiness of teachers to support the implementation of the 2013 Curriculum is in the moderate category, namely as many as 13 teachers (52%). Teachers fall into the low category as many as 10 teachers (40%) and teachers who fall into the high category are 2 teachers (8%). It can be concluded that the teacher's understanding and readiness in supporting the implementation of the 2013 curriculum are moderate.